Temperature-related chest pain presentations and future projections with climate change. (3rd October 2022) - Dawson, L; Andrew, E; Nehme, Z; Bloom, J; Cox, S; Anderson, D; Stephenson, M; Lefkovits, J; Taylor, A J; Kaye, D; Guo, Y; Smith, K; et al.
Abstract: Background: Climate change has led to increased interest in studying adverse health effects relating to ambient temperatures. It is unclear whether incident chest pain is associated with non-optimal temperatures and how chest pain presentation rates might be affected by climate change. Methods: The study included ambulance data of chest pain presentations in Melbourne, Australia from 1/1/2015 to 30/6/2019 with linkage to hospital and emergency discharge diagnosis data. A time series quasi-Poisson regression with a distributed lag nonlinear model was fitted to assess the temperature-chest pain presentation associations, after adjusting for season, day of the week and long-term trend. Future excess chest pain presentations associated with cold and heat were projected under six general circulation models under medium and high emission scenarios. Results: In 206, 789 chest pain presentations, mean (SD) age was 61.2 (18.9) years and 50.3% were female. Significant heat- and cold-related increased risk of chest pain presentations were observed for mean air temperatures above and below 20.8°C, respectively (Figure 1). Excess chest pain presentations related to heat were observed in all subgroups, but appeared to be attenuated for older patients (≥70 years) and patients of higher socioeconomic status (SES). We projected no significant change in net temperature-related chest pain presentations with climate change under medium- and high-emission scenarios, with increases in heat-related chest pain presentations offset by decreases in chest pain presentations related to cold temperatures. Conclusions: Heat- and cold-exposure appear to increase risk of chest pain presentations, especially among younger patients and patients of lower SES. In Melbourne, Australia, chest pain presentations overall were not projected to increase with climate change, but increases in heat-related chest pain presentations highlight the importance of risk mitigation strategies to minimise adverse health impacts on hotter days. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Alfred Health.